Domestic Public Debt of Externally Indebted Countries - Kumar, Manmohan (Occasional Papers; Occasional Paper ;, 1991)
This study discusses the evolution of domestic public debt in several indebted countries and its relationship with their external debt and underlying fiscal developments. It examines the links between domestic and external debt, taxes, subsidies, and government spending, and reviews strategies for managing domestic public debt.